Coping Strategies of Nursing Student against Academic and Clinical Stress at Public Sector Lahore - Yasmin, Samina; Hussain, Muhammad; Parveen, Kousar; Gilani, Syed Amir (International Journal of Social Sciences and Management, 2018)
Nursing is an emotionally demanding and a highly stressful profession as nurses has to deal with different people, in various situations and different times of the day. During their everyday work, they have to cope with extremely emotionally charged and rapidly changing circumstances. It is a universally accepted fact that human nature is prone to wears and tears associated with daily activities. These manifest in the form of stress and strains as witnessed in everyday life. Nurses and other healthcare professionals are exposed on daily basis to different levels of stress and burnout arising from the demand for their jobs. To explore the coping strategies of nursing student against clinical and academic stress. A quantitative, descriptive cross-sectional study design was used to explore coping strategies of nursing students against academic and clinical stress at public hospital Lahore. The instrument use for the data collection was adopted questioner and convenient sampling technique was used. The mean difference is significant at the 0.05 level. It is observed that academic and clinical stress sources and coping mechanisms are statistically significant, as p-value < 0.05. The present study was considered as a cornerstone that gives strong support towards coping strategies of nursing student against academic and clinical stress. It highlighted there are number of clinical and academic stress that hinder good performance of student. These results substantiate the belief that aspects of the practice environment affect student nurse academic performance and most importantly, the quality of care delivered on clinical placement to the patient. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 209-218